2015
DOI: 10.1681/asn.2014080793
|View full text |Cite
|
Sign up to set email alerts
|

EGF Receptor Inhibition Alleviates Hyperuricemic Nephropathy

Abstract: Hyperuricemia is an independent risk factor for CKD and contributes to kidney fibrosis. In this study, we investigated the effect of EGF receptor (EGFR) inhibition on the development of hyperuricemic nephropathy (HN) and the mechanisms involved. In a rat model of HN induced by feeding a mixture of adenine and potassium oxonate, increased EGFR phosphorylation and severe glomerular sclerosis and renal interstitial fibrosis were evident, accompanied by renal dysfunction and increased urine microalbumin excretion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
141
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 99 publications
(147 citation statements)
references
References 73 publications
4
141
0
1
Order By: Relevance
“…Using this model, they demonstrated that blockage of EGFR by gefitinib, a drug that specially inhibits EGFR activation and is clinically used for treating various cancers, alleviated renal fibrosis and renal tubular injury and inhibited activation of renal interstitial fibroblast, a pathological process that initiates the development of renal fibrosis and promotes its progression. 4 Mechanistically, inhibition of EGFR abrogated the expression of TGF-β and phosphorylation of Smad3 (a downstream molecule of TGF-β), and blocked NF-kB pathway activation and macrophage infiltration in the kidney of hyperuricemic rat. 4 In addition, gfitinib treatment decreased release of various proinflammatory cytokines/chemokines including TGFα, interleukin 1 beta (IL-1β), monocyte chemoattractant protein-1 (MCP-1) and RANTES.…”
Section: -7mentioning
confidence: 99%
See 4 more Smart Citations
“…Using this model, they demonstrated that blockage of EGFR by gefitinib, a drug that specially inhibits EGFR activation and is clinically used for treating various cancers, alleviated renal fibrosis and renal tubular injury and inhibited activation of renal interstitial fibroblast, a pathological process that initiates the development of renal fibrosis and promotes its progression. 4 Mechanistically, inhibition of EGFR abrogated the expression of TGF-β and phosphorylation of Smad3 (a downstream molecule of TGF-β), and blocked NF-kB pathway activation and macrophage infiltration in the kidney of hyperuricemic rat. 4 In addition, gfitinib treatment decreased release of various proinflammatory cytokines/chemokines including TGFα, interleukin 1 beta (IL-1β), monocyte chemoattractant protein-1 (MCP-1) and RANTES.…”
Section: -7mentioning
confidence: 99%
“…4 Mechanistically, inhibition of EGFR abrogated the expression of TGF-β and phosphorylation of Smad3 (a downstream molecule of TGF-β), and blocked NF-kB pathway activation and macrophage infiltration in the kidney of hyperuricemic rat. 4 In addition, gfitinib treatment decreased release of various proinflammatory cytokines/chemokines including TGFα, interleukin 1 beta (IL-1β), monocyte chemoattractant protein-1 (MCP-1) and RANTES. 4 Furthermore, blockage of EGFR reduced serum uric acid levels through inhibiting the activity of the enzyme xanthine oxidase, a key enzyme for the production of uric acid, as well as through preventing the downregulation of urate transporters, organic anion transporter 1 (OAT1) and OAT3.…”
Section: -7mentioning
confidence: 99%
See 3 more Smart Citations